2020
DOI: 10.3390/biom10111573
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibition by Intraperitoneal Dapagliflozin Mitigates Peritoneal Fibrosis and Ultrafiltration Failure in a Mouse Model of Chronic Peritoneal Exposure to High-Glucose Dialysate

Abstract: Peritoneal dialysis (PD) is limited by glucose-mediated peritoneal membrane (PM) fibrosis, angiogenesis, and ultrafiltration failure. Influencing PM integrity by pharmacologically targeting sodium-dependent glucose transporter (SGLT)-mediated glucose uptake has not been studied. In this study, wildtype C57Bl/6N mice were treated with high-glucose dialysate via an intraperitoneal catheter, with or without addition of selective SGLT2 inhibitor dapagliflozin. PM structural changes, ultrafiltration capacity, and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…No GLUT-1 inhibitor is currently available for use in humans ( Reckeh and Waldmann, 2020 ). The presence of SGLT-2 has been shown in peritoneal mesothelial cells of humans and mice ( Balzer et al, 2020 ). Their expression was upregulated by glucose containing dialysis fluids, which was prevented by SGLT-2 inhibition.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…No GLUT-1 inhibitor is currently available for use in humans ( Reckeh and Waldmann, 2020 ). The presence of SGLT-2 has been shown in peritoneal mesothelial cells of humans and mice ( Balzer et al, 2020 ). Their expression was upregulated by glucose containing dialysis fluids, which was prevented by SGLT-2 inhibition.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…ROS destroy PMC mitochondrial membrane integrity and reduce mitochondrial membrane potential (MMP). Moreover, ROS production is accompanied by an increase in intracellular DNA oxidative damage markers such as 8-hydroxydeoxyguanosine (8-OHdG) and a decrease in antioxidants such as glutathione (GSH) (Balzer et al, 2020). Our results showed that in rat PMCs, LY294002 and rapamycin prevented the increase of ROS levels stimulated by high-glucose peritoneal dialysate, increased the activity of GPX and GSH, and reduced the production of 8-OHdG and MDA.…”
Section: Discussionmentioning
confidence: 68%
“…Recent data shows that the total number of PD patients is increasing at an average annual rate of approximately 18% in China (Wu et al, 2016), indicating that PD is gradually becoming one of the main dialysis methods for kidney failure patients. However, the efficiency of PD gradually decreases with the time of PD prolonged and ultrafiltration failure (UFF) finally occurs, resulting in structural remodelling of the peritoneum, and PF (Balzer et al, 2020). It is currently known that epithelialmesenchymal transition (EMT) is the initial pathological change in PF.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2 inhibitors blocked TGF-β1-induced mRNA expression of thrombospondin 1 (THBS1), tenascinC(TNC), and platelet-derived growth factor subunit B (PDGF-B), which were key mediators of renal brosis and kidney disease progression in two human proximal tubular (PT) cell lines [21]. Dapagli ozin signi cantly reduced e uent TGF-β concentrations, peritoneal thickeningand brosis, resulting in improved ultra ltration in a mouse model of chronic peritoneal exposure to high-glucose dialysate [22].…”
Section: Discussionmentioning
confidence: 99%